A study of factors in influencing demands towards national car model in Malaysia: an empirical study from 1990-2004 / Khairul Mohd Yonan - Mohd Yonan, Khairul (Faculty of Business and Management, 2006)
This research paper attempts to determine the relationship between interest rate, population, CPI and gross domestic product (GDP) towards demand for national car model in Malaysia. The data is collected for 15 years starting from year 1990 to 2004 in quarterly basis. The methods used are Simple Linear Regression Model and Multiple Linear Regression Model. Based on analysis from simple linear regression model, the result shows that there are significant and no significant relationships between interest rate, population, CPI and GDP with demand for national car model in Malaysia. The result also shows that there are positive relationships between Base Lending Rate and consumer Price Index, meanwhile for population and gross domestic product, the result shows a negative relationship between demands for national car model in Malaysia. Under the multiple linear regression models, the result shows that all selected variables (interest rate, population, CPI and GDP) have no significant relationships with demand for national car model in Malaysia simultaneously